PENGARUH PENGENDALIAN BIAYA DAN PENGELOLAAN ANGGARAN TERHADAP KINERJA ORGANISASI BIDANG PELAYANAN DOKUMEN PERJALANAN PADA KANTOR IMIGRASI KELAS I KHUSUS NON TPI JAKARTA BARAT - Achmad Asyraq Fadhillah (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to analyze the influence of cost control and budget management on organizational performance in the Travel Document Service Division at the Class I Special Non-TPI Immigration Office of West Jakarta. Employing a quantitative approach with a survey method, the research involved 91 employees as respondents. Data were collected using a structured questionnaire designed to measure variables of cost control, budget management, and organizational performance. The results indicate that cost control has a positive and significant effect on organizational performance, with a regression coefficient of 0.40. Budget management also shows a significant effect on organizational performance, with a regression coefficient of 0.35. Collectively, these two variables explain 51.6% of the variance in organizational performance, measured through indicators such as employee productivity, profitability, responsiveness, problem-solving, and reputation. This study highlights the importance of efficient cost control and budget management in maximizing organizational performance within the public sector. The findings provide practical implications for government institutions in enhancing the effectiveness and efficiency of public service delivery amid dynamic and changing circumstances.